2014
DOI: 10.1111/acer.12481
|View full text |Cite
|
Sign up to set email alerts
|

Intoxication‐ and Withdrawal‐Dependent Expression of Central and Peripheral Cytokines Following Initial Ethanol Exposure

Abstract: Background Evidence has emerged demonstrating that ethanol influences cytokine expression within the CNS, although most studies have examined long-term exposure. Thus, the cytokine response to an acute ethanol challenge was investigated, in order to characterize profiles of cytokine changes following acute exposure. Methods Rats pups were injected intraperitoneally (i.p.) with 2-g/kg ethanol and IL-1 mRNA and protein assessed 0, 60, 120, 180, and 240 min post-injection (Exp. 1). In Exps. 2-5, the expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
83
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 47 publications
10
83
0
Order By: Relevance
“…ethanol as potential drivers of endotoxin transit into blood, and whether such responses might differentially impact the action of ethanol on brain cytokines following these two commonly used modes of ethanol administration. Our a priori hypothesis was that ethanol exposure (regardless of route or age) would evoke central cytokine changes consistent with our previous findings (i.e., increased IL-6, decreased IL-1 and TNF; see [39]), and that these changes would occur independent of plasma endotoxin alterations. Together, the side-by-side comparison of LPS and ethanol challenge with multiple, within-subject, physiological measures (e.g., plasma measures of corticosterone, endotoxin, and blood ethanol content; plus cytokine measures in several key CNS structures) was expected to fully elucidate the nature of age-related differences in neuroimmune consequences of ethanol, and to inform future directions for identifying the mechanisms underlying any developmental differences observed.…”
Section: Introductionsupporting
confidence: 64%
See 3 more Smart Citations
“…ethanol as potential drivers of endotoxin transit into blood, and whether such responses might differentially impact the action of ethanol on brain cytokines following these two commonly used modes of ethanol administration. Our a priori hypothesis was that ethanol exposure (regardless of route or age) would evoke central cytokine changes consistent with our previous findings (i.e., increased IL-6, decreased IL-1 and TNF; see [39]), and that these changes would occur independent of plasma endotoxin alterations. Together, the side-by-side comparison of LPS and ethanol challenge with multiple, within-subject, physiological measures (e.g., plasma measures of corticosterone, endotoxin, and blood ethanol content; plus cytokine measures in several key CNS structures) was expected to fully elucidate the nature of age-related differences in neuroimmune consequences of ethanol, and to inform future directions for identifying the mechanisms underlying any developmental differences observed.…”
Section: Introductionsupporting
confidence: 64%
“…A single peak expressed as the negative first derivative of the change in fluorescence as a function of temperature indicated primer specificity to the target gene. Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) was used as a reference gene in these experiments, as studies from our laboratory have revealed more stable gene expression across ethanol treatment conditions with this gene [e.g., 39]. Primer sequences and a brief description of gene function can be found in Table 1.…”
Section: General Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have made use of radioimmunoassay have successfully found increases in met-enkephalin, the endogenous ligand for the DOR, within the nAC and hypo following a similar prenatal manipulation [34]. While future studies will be necessary to clarify the reasons for the dissociation between mRNA and protein observed here, such effects are common (e.g., [48] and [49], but see [50]) and underscore the importance of examining both mRNA and protein as a function of experimental treatment. Regardless, the present data provide important information regarding functional plasticity of the opioid system across early ontogeny and highlight the vulnerability of this system to prenatal programming effects of PAE.…”
Section: Discussionmentioning
confidence: 92%